2019
DOI: 10.1080/21635781.2019.1580642
|View full text |Cite
|
Sign up to set email alerts
|

Social and Psychological Risk and Protective Factors for Veteran Well-Being: The Role of Veteran Identity and Its Implications for Intervention

Abstract: Social psychological theory hypothesizes that one’s identity, self-definitions, and meanings used for a particular social role fosters individual purpose in life and affects behavior in specific social situations. As such, it can be protective against the onset of psychological disorders. We examined this hypothesis with data collected from 1,730 military veterans recruited to study the health effects of warzone deployments. The sample was primarily male, older, and White. Our key independent variable was a Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…14,15 As described below, the genetic risk factors for PTSD that we assessed were among outpatients, all of whom were formerly deployed military veterans receiving care in a large multi-hospital system in central Pennsylvania. [16][17][18][19] Although the number of veterans in these settings with PTSD has varied, about 7-10% of them have been diagnosed with current PTSD in recent years, 16,18,20 which is consistent with the prevalence rate in the current study.…”
Section: Introductionsupporting
confidence: 85%
“…14,15 As described below, the genetic risk factors for PTSD that we assessed were among outpatients, all of whom were formerly deployed military veterans receiving care in a large multi-hospital system in central Pennsylvania. [16][17][18][19] Although the number of veterans in these settings with PTSD has varied, about 7-10% of them have been diagnosed with current PTSD in recent years, 16,18,20 which is consistent with the prevalence rate in the current study.…”
Section: Introductionsupporting
confidence: 85%
“…This study also highlights the need for future research to understand further how identity influences veterans' experiences in recovery homes and other community settings. Finally, future studies would benefit from employing mixed-method research that includes a measure of veteran identity centrality (see Adams et al, 2019) to augment further what is learned from qualitative accounts. Future investigations should also examine how the veteran identity interplays with other identities (e.g., racial/ethnicity, gender) to impact veterans' integration into OH.…”
Section: Discussionmentioning
confidence: 99%
“…Although veterans are diverse individuals who belong to multiple social groups and backgrounds, for many, the veteran identity is particularly salient and central to their self‐concept (Adams et al, 2019; Atuel & Castro, 2018; Brunger et al, 2013; Harada et al, 2005). For instance, among 1730 veterans receiving health services from the Department of Veterans Affairs (VA) and Non‐VA medical healthcare centers, over 50% scored very high on a veteran identity centrality scale (Adams et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Prior trauma-related studies have assessed the relationships of demographic variables (e.g., race, age, gender, education level) to happiness (Morgan et al, 2017) as well as the time since a traumatic event and number of traumatic events (Adams et al, 2019). Morgan et al (2017) found education level to be positively related to happiness.…”
Section: Demographicsmentioning
confidence: 99%
“…Responses ranged from 1 = less than 6 months ago, to 14 = over 50 years ago. Such retrospection is common in military-focused TE research (Adams et al, 2019;Tsai et al, 2015).…”
Section: Most Powerful Prior Traumatic Event (Te)mentioning
confidence: 99%